Endoplasmic reticulum stress induces growth retardation by inhibiting growth hormone IGF-I axis. (December 2020) - Xia, Wanjun; Wang, Yajun; Zhang, Yong; Ge, Xin; Lv, Pengwei; Cheng, Jingliang; Wei, Juncheng
Abstract: Objective: Insulin-like growth factor 1 (IGFI) is one of several growth factors which is induced by growth hormone (GH), which activates the Janus kinase 2 (JAK2)-signal transducer and activator of transcription 5 (STAT5) pathway, and plays crucial roles in normal human growth, metabolism, and systemic energy homeostasis. However, little is known about the negative regulation of IGF-I production under different physiological or pathological conditions. Herein, we explore whether activation of endoplasmic reticulum (ER) stress regulates IGF-I production and normal body growth. Materials and methods: C57BL/6 J mice were challenged with tunicamycin (Tm) to induce ER stress activation. 24 h after stimulation, hepatic mRNA expression was analyzed by RNA-Seq and validated by qPCR. Enzyme-linked immunosorbent assay (ELISA) was performed 24 h after Tm stimulation. Body growth was determined 16 days after Tm stimulation. Animals were then sacrificed and liver tissues were collected for further analysis. Results: Mice challenged with Tm displayed a retardation of growth. Molecularly, we found that ER stress inhibited phosphorylation of STAT5. IGF-I transcription and circulating IGF-I were also dramatically decreased under ER stress activation. Moreover, our results demonstrate that IGF-I administration ameliorates Tm-induced growth retardation. Conclusions: ER stress induces growth retardation. ER stress inhibits hepatic GH-JAK2 signaling activation and its downstream target gene expression. These results warrant further research to explore the crosstalk between ER stress and growth hormone signaling in improving body growth. Highlights: ER stress could inhibit whole body growth. ER stress negatively regulates growth hormone-hepatic JAK2-STAT5 signaling activation. ER stress could inhibit IGF1 transcription and production.